2016
DOI: 10.18203/2349-2902.isj20160665
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of preoperative predictive factors that determine difficult laparoscopic cholecystectomy

Abstract: The advantages of laparoscopic cholecystectomy over open cholecystectomy are earlier return to bowel functions, less postoperative pain, better cosmetic outcome, shorter length of hospital stay, earlier return to full activity, and decreased overall cost. Laparoscopic cholecystectomy is associated with better preservation of ABSTRACT Background: Cholelithiasis is the most common biliary pathology. Gallstones are present in 10 to 15% of the general population and asymptomatic in the majority (>80%). The prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Patil et al studied on 50 patients and found impacted stone was not a significant criterion for difficult LC (p>0.3). 7 Suryawanshi et al (600 patients) reported that this was a significant criterion. 32 Siddiqui et al studied on 300 patients and also found presence of impacted stone was significant (p<0.05).…”
Section: Usg Findingsmentioning
confidence: 98%
“…Patil et al studied on 50 patients and found impacted stone was not a significant criterion for difficult LC (p>0.3). 7 Suryawanshi et al (600 patients) reported that this was a significant criterion. 32 Siddiqui et al studied on 300 patients and also found presence of impacted stone was significant (p<0.05).…”
Section: Usg Findingsmentioning
confidence: 98%
“…Variables such as age, sex, and impacted stones were not found to be significant predictors. However, they mention that in the case of men they may outperform women, due to sociocultural factors that predispose a late attendance to medical centers [35]. In addition, Chávez Segura stated the results of studies in relation to sex should be considered inconclusive, because most of the population that goes to hospitals are mostly female [36], which we take as a reservation because it is more frequent in women.…”
Section: Hayama Et Al Mention That the Risk Factors For Conversion De...mentioning
confidence: 99%
“…In relation to sex, Shreenath et al do not consider it as a predictor, but report that conversion secondary to difficult cholecys-tectomy is frequent in patients with history of hospitalization, previous abdominal surgeries, palpable gallbladder, BMI greater than 27.5 kg/m2 and thickened gallbladder wall. Sex, age, and impact calculation were not identified as predictors [14,15]. In summary, the prevalence of cholelithiasis in Mexico is 14.3%, of which 8.5% are men and 20.5% are women; obesity has been reported to be associated with a cholelithiasis elevated risk [16] and as an important factor in the conversion of LC [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Previous episodes of hospitalisation was found to be a statistically significant risk factor for conversion. 1,2,7,9,10,12 This was presumed due to more adhesions at the Calot's triangle due to adhesions. Signs of acute cholecystitis were investigated by authors either with clinical signs or laboratory parameters like WBC count.…”
Section: Clinical Parameters-disease Factorsmentioning
confidence: 99%
“…The impacted stone was found to be a significant risk factor for conversion. 9,10,12 The size of the stone was investigated by Jethwani et al and found to be a significant factor. 8 Larger stones increased the risk of difficulty and conversion.…”
Section: Radiological Parametersmentioning
confidence: 99%